Ancestral state reconstruction infers phytopathogenic origins of sooty blotch and flyspeck fungi on apple. (1st March 2016) - Ismail, Siti Izera; Batzer, Jean Carlson; Harrington, Thomas C.; Crous, Pedro W.; Lavrov, Dennis V.; Li, Huanyu; Gleason, Mark L.
Abstract : Members of the sooty blotch and flyspeck (SBFS) complex are epiphytic fungi in the Ascomycota that cause economically damaging blemishes of apples worldwide. SBFS fungi are polyphyletic, but approx. 96% of SBFS species are in the Capnodiales. Evolutionary origins of SBFS fungi remain unclear, so we attempted to infer their origins by means of ancestral state reconstruction on a phylogenetic tree built utilizing genes for the nuc 28S rDNA (approx. 830 bp from near the 59 end) and the second largest subunit of RNA polymerase II ( RPB2 ). The analyzed taxa included the well-known genera of SBFS as well as non-SBFS fungi from seven families within the Capnodiales. The non-SBFS taxa were selected based on their distinct ecological niches, including plant-parasitic and saprophytic species. The phylogenetic analyses revealed that most SBFS species in the Capnodiales are closely related to plant-parasitic fungi. Ancestral state reconstruction provided strong evidence that plant-parasitic fungi were the ancestors of the major SBFS lineages. Knowledge gained from this study may help to better understand the ecology and evolution of epiphytic fungi.